A global analysis of urban design types and road transport injury: an image processing study. Issue 1 (January 2020) - Thompson, Jason; Stevenson, Mark; Wijnands, Jasper S; Nice, Kerry A; Aschwanden, Gideon DPA; Silver, Jeremy; Nieuwenhuijsen, Mark; Rayner, Peter; Schofield, Robyn; Hariharan, Rohit; Morrison, Christopher N
Summary: Background: Death and injury due to motor vehicle crashes is the world's fifth leading cause of mortality and morbidity. City and urban designs might play a role in mitigating the global burden of road transport injury to an extent that has not been captured by traditional safe system approaches. We aimed to determine the relationship between urban design and road trauma across the globe. Methods: Applying a combined convolutional neural network and graph-based approach, 1692 cities capturing one third of the world's population were classified into types based on urban design characteristics represented in sample maps. Associations between identified city types, characteristics contained within sample maps, and the burden of road transport injury as measured by disability adjusted life-years were estimated through univariate and multivariate analyses, controlling for the influence of economic activity. Findings: Between Mar 1, 2017, and Dec 24, 2018, nine global city types based on a final sample of 1632 cities were identified. Burden of road transport injury was an estimated two-times higher (risk ratio 2·05, 95% CI 1·84–2·27) for the poorest performing city type compared with the best performing city type, culminating in an estimated loss of 8·71 (8·08–9·25) million disability-adjusted life-years per year attributable to suboptimal urban design. City types that featured a greater proportion of railed public transport networks combined with dense road networks characterised by smaller blocks showed the lowest rates of road traffic injury. Interpretation: This study highlights the important role that city and urban design plays in mitigating road transport injury burden at a global scale. It is recommended that road and transport safety efforts promote urban design that features characteristics inherent in identified high-performance city types including higher density road infrastructure and high rates of public transit. Funding: See acknowledgments.